Seven new species of Tetranemertes Chernyshev, 1992 (Monostilifera, Hoplonemertea, Nemertea) from the Caribbean Sea, western Pacific, and Arabian Sea, and revision of the genus - Cherneva, Irina (2023)
The marine ribbon worm genus Tetranemertes Chernyshev, 1992 currently includes three species: the type species T. antonina (Quatrefages, 1846) from the Mediterranean Sea, T. rubrolineata (Kirsteuer, 1965) from Madagascar, and T. hermaphroditica (Gibson, 1982) from Australia. Seven new species are described: T. bifrost sp. nov., T. ocelata sp. nov., T. majinbuui sp. nov., and T. pastafariensis sp. nov. from the Caribbean Sea (Panamá), and three species, T. unistriata sp. nov., T. paulayi sp. nov., and T. arabica sp. nov., from the Indo-West Pacific (Japan and Oman). As a result, an amended morphological diagnosis of the genus is offered. To improve nomenclatural stability, a neotype of Tetranemertes antonina is designated from the Mediterranean. The newly described species, each char-acterized by features of external appearance and stylet apparatus, as well as by DNA-bar-codes, form a well-supported clade with T. antonina on a molecular phylogeny of monostil-iferan hoplonemerteans based on partial sequences of COI, 16S rRNA, 18S rRNA, and 28S rRNA. Six of the seven newly described species, as well as T. rubrolineata, possess the unusual character of having a central stylet basis slightly bilobed to deeply forked poste-riorly in fully grown individuals, a possible morphological synapomorphy of the genus. In addition, an undescribed species of Tetranemertes is reported from the Eastern Tropical Pacific (Panamá), increasing the total number of known species in the genus to eleven.